The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1227/01.neu.0000192167.54627.3a
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative Activity through Extracellular Signal-regulated Kinase of Smooth Muscle Cells in Vascular Walls of Cerebral Arteriovenous Malformations

Abstract: pERK was detected in smooth muscle cells of the vascular walls of AVMs. It may function in the proliferative activity of smooth muscle cells. Vascular remodeling through pERK may play an important role in the growth and maintenance of cerebral vascular malformations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Caspasedependent apoptosis and overproduction of matrix metalloproteinase have been implicated as contributory mechanisms in the associated degradation or remodeling of the arterial wall. 12,13 Therefore, diffuse and severe thinning of the wall area in our patients with MMD with could represent media shrinkage, which was not observed in our patients with ICAD.…”
Section: Discussionmentioning
confidence: 63%
“…Caspasedependent apoptosis and overproduction of matrix metalloproteinase have been implicated as contributory mechanisms in the associated degradation or remodeling of the arterial wall. 12,13 Therefore, diffuse and severe thinning of the wall area in our patients with MMD with could represent media shrinkage, which was not observed in our patients with ICAD.…”
Section: Discussionmentioning
confidence: 63%
“…17 In and around the vessel walls of AVMs, various growth factors, including vascular endothelial growth factor, basic fibroblast growth factor, and transforming growth factor-b 1 , are observed. [18][19][20] Proliferation-related transcription factors, such as hypoxia-inducing factor and extracellular signal-regulated protein kinase, are expressed, 21,22 and endothelial proliferation takes place in vascular walls. 21 Cell death (via apoptotic pathways) is also detected in the vessel walls of cerebral AVMs.…”
Section: Discussionmentioning
confidence: 99%
“…1,8,25,89 After stimulation, ERK induces cellular proliferation and transformation. 25,89,110,134 Takagi and colleagues 124 have suggested that the activation of the ERK pathway depends on the chronic increase in blood flow within the vasculature. It has been well established that chronic increases in blood flow can upregulate shear-induced genes, which induce vascular remodeling.…”
mentioning
confidence: 99%